1969
DOI: 10.12669/pjms.324.9384
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Mammography in Diagnosis and Identification of breast Mass

Abstract: Objective:To study the effect and clinical value of mammography in the diagnosis of breast lump so as to improve the diagnosis level of breast cancer.Methods:A retrospective analysis was carried out on clinical data of 110 patients with mammary lump confirmed by pathology to study the compliance of mammography diagnosis and Pathology diagnosis in breast lump, and the detection of microcalcifications, phyllode, and observe the image performance of mammography. Taking infitrating ductal carcinoma (IDC) as an exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Infiltrating ductal carcinoma was the most frequent type of BC found in our study, which is quite in line with studies conducted in different regions in other countries. 18,19 MMG confirms malignant lesion based on the shape, size, margins of lump and number and distribution of calcification. In our study, we confirmed malignant cases through irregular shape and well-defined margins of the lesions.…”
Section: Discussionmentioning
confidence: 84%
“…Infiltrating ductal carcinoma was the most frequent type of BC found in our study, which is quite in line with studies conducted in different regions in other countries. 18,19 MMG confirms malignant lesion based on the shape, size, margins of lump and number and distribution of calcification. In our study, we confirmed malignant cases through irregular shape and well-defined margins of the lesions.…”
Section: Discussionmentioning
confidence: 84%
“…While necessary to remove these irregularities, acknowledging they are likely to be a source of increased false positives, it is important to limit the number of points discarded, to avoid tumors close to the nipple or chest wall being missed. Tumors developing near the chest wall are also an existing challenge in mammography due to difficulties in obtaining sufficient breast compression close to the chest wall to allow x-ray penetration ( 49 ).…”
Section: Methodsmentioning
confidence: 99%
“…about clinical value of mammography in diagnosis and identification of breast tumors, mentioned that the sensitivity, specificity and accuracy of mammography was 90.80%, 84.60%, and 87.40%, which means that mammography has a significant clinical value in diagnosing and identifying breast tumors. [10] The diagnosis of breast abnormalities imaging used the Breast Imaging and Reporting System (BI-RADS) mammography which was proposed by the American College of Radiology (ACR) in 1993, and currently the latest edition of BI-RADS is the 5th edition published in 2013. [11] Based on BI-RADS 5th edition, BI-RADS assessment are categorized from 0 to 6, in which 0 means incomplete, 1 means negative, 2 means benign findings, 3 means probably benign, 4 means suspicious abnormality, 5 means highly suspicious of malignancy , and 6 means known biopsy proven malignancy.…”
Section: Introductionmentioning
confidence: 99%